Performance of novel high throughput multi electrospray systems for forming of polymeric micro/nanoparticles. (15th July 2017) - Parhizkar, M.; Reardon, P.J.T.; Knowles, J.C.; Browning, R.J.; Stride, E.; Pedley, R.B.; Grego, T.; Edirisinghe, M.
Abstract: In order to maintain a stable cone-jet mode in electrospray low flow rates are used while most applications require a high throughput. We compare two different designs of the multiple electrospray system in order to increase the output for large scale production applications. In this study, the solution was fed through four separate needles that were attached to either a circular or a rectangular metallic plate that were connected to a high voltage DC power supply. The behaviour of the electrospray jets as well as the deposition of particles were investigated. It was shown that the throughput of particles was increased while particles with narrow size distribution were produced from all four uniform electrospray jets. Highlights: Two new multi needle electrospraying geometries were tested. The basis in designing the multi needle systems was to operate all four needles with stable cone jet. Particles were produced at higher rates for the same collection period compared with single needle electrospraying. The electrospraying jets were visualized with a high-speed camera and the electrospray jet evolution was studied in detail. Graphical abstract: